H. Zh. Harutyunyan – Pertsh Sergeevich Boshnaghyan: Essays from Military, Scientific and Public-Political Activities or MEMENTO VIVERE. Yerevan, Publishing House “Limush”, 2022, 200 p. - Hovhannisyan, Haykaz (History and Culture, 2022)
The review briefly presents an analysis of all the priority problems addressed by the author of the monograph H.Zh. Harutyunyan. A focus has been made on the military career of P.S. Boshnagyan and his scientific and socio-political (deputy of the National Assembly of the Republic of Armenia) activities. The book received our high appraisal as an extremely important work, which presents the image of a true citizen of his country, devoted to the ideals of the Motherland. It is no coincidence that the prefaces to the monograph by H.Zh. Harutyunyan were written by prominent figures of our time – Lieutenant-General M.G. Grigoryan, Dean of the Faculty of Geology and Geography M.A. Grigoryan, as well as the Director of the Center of Russian Studies at the Faculty of International Relations of YSU, deputy of the National Assembly of the RA of the 4th convocation A.V. Safaryan.
Keywords: P.S. Boshnaghyan; H.Zh. Harutyunyan; geology; Yerevan State University; National Assembly of the Republic of Armenia; scientific research; nature protection